Курган доби бронзи коло села Гродзеве на Уманщині - Куштан, Д.П. (Археологія і давня історія України, 2021)
Стаття присвячена публікації матеріалів розкопок кургану поблизу села Гродзеве Уманського
району Черкаської області. Всі 10 виявлених поховань відносяться до доби бронзи: вісім — до ямної
культури, 2 — до культурного кола Бабине (Дніпро-Прутської бабинської культури). This paper presents the data from the excavation
of the kurgan 6 near the village of Grozdeve in Uman
region of the Cherkasy oblast. The complex was investigated
by the Expedition of the Cherkasy Archaeological
Rescue Surveys in 2011. This kurgan was a component
of the large kurgan group located to the east
and north-east from the village of Grozdeve, near the
road Uman — Kirovohrad in the direction of the village
of Babanka. Topographically the kurhan cemetery is
located on top of the watershed of the rivers Umanka
(from the west) and Revukha (from the east), which flow
into the Yatran river (basing of the Southern Buh).
Kurhan 6 was located in the central part of the group.
The southern part of the kurgan was partly destroyed
by the road, which was built in 1950s. Initially the elevation
of kurgan reached 2.5—3 m. By the moment of
excavations its elevation reached 1.3—1.5 m, and the diameter
was measured to 35—40 m. The kurgan included
ten burials of the Bronze Age. Eight of those belong to
the Yamna culure (3rd mil. BC), two others were attributed
to the Babyne cultural complex (the first half of the
2nd mil. BC). Despite the significantly destroyed mound,
profiles preserved the stratigraphy of the kurgan. The
buried soil and at least two mounds were identified.
Yamna burials are similar to the Southern Buh
variation of the Yamna culutural complex by its ritual:
nearly rectangular pits covered with wood, remains of
bark on the floor, position of skeletons, burials of two
people, western and eastern orientation of buried, use
of ochre etc. Two burials included ceramic pots with a
short neck, egg-shaped body and sharp bottom. Those
are dated to the late period of Yamna culture.
Babyne burials do not have significant features. Both
are characterized by nearly rectangular pits of a small
size and depth, organic remains on the floor and wooden
constructions in burials, eastern orientation of buried,
the lack of inventory. These burials are dated to the late
period of the culture (Dnipro-Prut Babyne culture).